Isolated Intracranial Rosai-Dorfman Disease - Md. Taufiq; Abul Khair; Ferdousy Begum; Shabnam Akhter; Md. Shamim Farooq; Mohammed Kamal (Case Reports in Neurological Medicine, 2016)
Background. Rosai-Dorfman disease (RDD) is a benign histiocytic proliferative disorder of unknown etiology. This rare condition commonly causes massive cervical lymphadenopathy. Intracranial RDD without any nodal involvement is extremely rare. Case Report. A young Bangladeshi male complained of bilateral complete blindness with left sided deafness for about three years. There was no lymphadenopathy. MRI and CT scan of brain suggested an inflammatory/neoplastic (?meningioma) lesion located at left parasellar region which extended frontally to encircle both optic nerves and also to left prepontine area. Histopathologically the lesion was diagnosed as RDD. The patient was treated with steroid and significant clinical improvement observed. Conclusion. The prognosis of intracranial RDD is not poor. It can be treated with surgery with or without corticosteroids, chemotherapy, and so forth. But as the condition is extremely rare and often misdiagnosed, the clinician, radiologist, and histopathologist should have a suspicion in their mind about the possibility of RDD.